Is the ASEAN-Korea Free Trade Area (AKFTA) an Optimal Free Trade Area? - Donghyun Park; Innwon Park; Gemma Esther B. Estrada (Asian Development Bank (ADB), 2008)
The 1997/98 Asian currency crisis has led a once high-flying East Asia to realize its vulnerability to external shocks. This realization has given strong impetus to greater economic integration among East Asian economies, with the ASEAN-Korea Free Trade Area (AKFTA) a case in point. This paper qualitatively and quantitatively examines the economic feasibility of AKFTA: qualitatively using the theory of economic integration, and quantitatively by applying a CGE model. Our two-dimensional analysis provides some, but not overwhelming, support for AKFTA's prospects as an effective means of promoting trade between ASEAN and the Republic of Korea.
hdl:11540/1788
Keywords: F10; F14; F15; 330; ASEAN; Korea; trade; free trade area; economic integration